DEVELOPMENT OF A COMPREHENSIVE PEDESTRIAN FOOTBRIDGE MANAGEMENT SYSTEM - Munyaneza, Claude Munyaneza; Mbereyaho, Leopold (Journal of Civil Engineering, Science and Technology, 2020)
The footbridges in rural areas have been crucial as the only mean to overcome the rural isolation and allow breaking the cycle of poverty by providing access to such development facilities like education opportunities, markets, medical clinics and other basic services. In Rwanda, under collaboration with Engineers without Borders from German, and International Non-Government Organization Bridge to Prosperity (B2P, some footbridges are already built. In line with the agreement with B2P around 355 bridges are also planned in 5 years. The key challenge is to optimally allocate resources in order to maintain this number of bridges, especially under the current financial constraints. The purpose of this paper was to investigate and propose a pedestrian footbridge management system for Rwanda (PFBMS) which should allow the efficient bridge management, through the analysis of condition data, determination of the ranking and priority of bridge maintenance activities, as well as evaluation of the alternatives of preservation or replacement. The methodology comprises of the use of interview and discussions with district engineers in charge of bridge management, local community using the constructed footbridges as well as bridge builders from B2P. Microsoft Excel analysis tool has been used to developing the deterioration model, and therefore the PFBM was proposed. It is concluded that this system can accurately predict optimal maintenance planning as well as bridge rating.